교양영어수업에서 영어 프레젠테이션을 위한 PBL 수업사례 및 효과성 연구 - 임희주(Heejoo Im), 손희정(Heejung Son) (영어어문교육, 2024)
This study aims to examine the effectiveness of using Problem-Based Learning (PBL) teaching methods for English presentations in general English classes. The study involved 85 first-year university students. A descriptive analysis was conducted using SPSS on pre- and post-achievement tests and a post-survey regarding PBL effectiveness. Qualitative responses from reflection journals on PBL activities were also analyzed. The study’s results are as follows. First, the pre- and post-English achievement tests found statistically significant evidence that students improved through PBL activities. Second, the post-survey showed that students had high results in skills related to communication, self-direction, knowledge utilization, and problem-solving, but their English confidence was relatively low. Lastly, reflection journals revealed that students felt capable of participating in self-directed learning and exhibited more confidence in English presentations by developing the aforementioned skills. The implications of this study’s results are as follows. To improve self-directed learning, it is necessary to develop a PBL-based customized E curriculum and plan learning activities step-by-step to help learners adapt to tasks. Furthermore, to improve English confidence, it is recommended to design intermediate stages to provide feedback and opportunities to use English. Finally, it is appropriate for instructors to apply process-oriented evaluation methods to observe learner development. KCI Citation Count: 0